2016
DOI: 10.1002/jso.24246
|View full text |Cite
|
Sign up to set email alerts
|

An intraoperative MRI system for margin assessment in breast conserving surgery: Initial results from a novel technique

Abstract: This study demonstrates that the system is sensitive and specific in differentiating malignant and non-malignant tissues in freshly excised breast specimen. The system has the potential to be used for breast specimen margin assessment during BCS, with the goal of decreasing the need for re-operation. J. Surg. Oncol. 2016;114:22-26. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Overall, to date, these methods offer a modest increase in sensitivity but have a lower specificity. 27 30 Intraoperative pathology analysis in the form of gross specimen analysis or frozen section is used as routine practice at a small number of high-volume institutions to assess margin status. 8 , 31 , 32 Studies have shown that intraoperative frozen section pathology assessment yields highly accurate results comparable with those of permanent pathology and significantly reduces re-excision rates.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, to date, these methods offer a modest increase in sensitivity but have a lower specificity. 27 30 Intraoperative pathology analysis in the form of gross specimen analysis or frozen section is used as routine practice at a small number of high-volume institutions to assess margin status. 8 , 31 , 32 Studies have shown that intraoperative frozen section pathology assessment yields highly accurate results comparable with those of permanent pathology and significantly reduces re-excision rates.…”
Section: Discussionmentioning
confidence: 99%
“…This finding likely reflects the increased concordance between surgeon and pathologist when using the intraoperative inking technique, allowing surgeons to better target the area of potential residual disease at re‐excision. While strategies for real‐time intraoperative margin assessment are being developed and are used in select institutions, they are not widely implemented; therefore, accurate margin marking and assessment remains crucial in improving outcomes in BCS. Further longitudinal studies are needed to corroborate this finding and improve the accuracy of margin assessment.…”
Section: Discussionmentioning
confidence: 99%
“…The above measurements were taken on a small group of 22 subjects undergoing BCT. Therefore, the results require confirmation in further studies [32].…”
Section: Radiological (Imaging) Techniquesmentioning
confidence: 92%